Energy Harvesting Systems Principles, Modeling and Applications - Kazmierski, Tom J.; Beeby, Steve (Springer New York, 2011)
Energy Harvesting Systems: Principles, Modelling and Applications Edited by: Tom Kazmierski Steve Beeby Kinetic energy harvesting converts movement or vibrations into electrical energy, enables battery free operation of wireless sensors and autonomous devices and facilitates their placement in locations where replacing a battery is not feasible or attractive. This book provides an introduction to operating principles and design methods of modern kinetic energy harvesting systems and explains the implications of harvested power on autonomous electronic systems design. It describes power conditioning circuits that maximize available energy and electronic systems design strategies that minimize power consumption and enable operation. The principles discussed in the book are supported by real case studies such as battery-less monitoring sensors at water waste processing plants, embedded battery-less sensors in automotive electronics and sensor-networks built with ultra-low power wireless nodes suitable for battery-less applications. Provides a comprehensive introduction to energy harvesting systems; Covers the operating principles, design methods and real applications; Enables low-power autonomous electronic systems design.